Developing The Expectations of Motherhood Scale: Identifying maternal expectations and symptoms of depression and anxiety during pregnancy - Best, Ida (Curtin University, 2022)
This research focused on investigating the expectations that pregnant women hold about motherhood, and the association with self-efficacy, clinical perfectionism, and symptoms of depression and anxiety. The primary outcome of this project was the design of a valid and reliable measure, the Expectations of Motherhood Scale. The accurate identification of unrealistic expectations during pregnancy may contribute to identification and facilitate early intervention for women at risk of developing perinatal mental health difficulties.